New Lysianassoid Amphipods from the North Eastern Atlantic Ocean - Kaim-Malka, R. A. (Zootaxa, 2014)
Two new lysianassoid amphipod species, Ambasia anophthalma n. sp. and Bathyamaryllis biscayensis n. sp., are described based on adult females collected in the North Eastern Atlantic Ocean (Bay of Biscay) by an autonomous bait system deployed on the sea bottom at a depth of 1460–1550 m. These two species are characterized by the absence of eyes (blind species). They belong to genera which include very few species.